The structure of the alienated character in the narrative film (Al-Academy, 2025)
The topic of alienation is one of the philosophical, social and psychological problems that has been widely researched in contemporary human thought, and in various aspects of literature, philosophy, arts, sociology, economics and others. The concepts of alienation have become popular in cinema, and artistic trends have focused on the alienated character, as an image that reflects what contemporary man suffers from the pressures of technological tendencies that lead to marginalization and crushing of human existence and isolating him from the capabilities that control the world's systems and theories of control. The importance of the research also lies in the feasibility of employing the structure of the alienated character in the narrative film and the extents that this character can reach. As for the goal of this study, it was represented in studying the case of alienation in cinema, and studying the structure of the alienated character and its distinguished role in the narrative film. The theoretical framework included three topics: the first: alienation... the term and concept, the second: the structure of the alienated character, and the third topic: the alienated character in the narrative film. The third chapter contained the research methodology and the research sample, as well as the analysis of samples, and the research concluded with the results, conclusions, recommendations and a list of sources